Does Anonymity Matter? A Discoursal Study of Gender Recognition on Arabic Facebook Comments - Al-Sa’ati, Nashwan Mustafa (Issues in Language Studies, 2019)
This study considered the recognition of persons’ gender through the differences of the discoursal features and stylistic choices of their Arabic Facebook comments. Three hundred comments on different topics were collected from same-/cross-sex interactions of friends, acquaintances and relatives having similar educational and social backgrounds and with an age range 20- 50. Some research questions were raised as to whether males and females differed in terms of the discoursal features of their comments as well as the ability to recognize the person’s gender on the basis of these features. Accordingly, some hypotheses were formulated, viz. males’ and females’ comments involved distinguished gendered discoursal features and styles, females behaved in line with maintenance roles while males behaved in line with task- oriented roles, and the persons’ gender could be predicted through applying the gendered features they had. The study came up with various conclusions that, to some extent, confirmed the hypotheses stated.